2008
DOI: 10.1177/0145445508318846
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the On-Task Homework Behavior of Youth With Behavior Disorders Using Functional Behavioral Assessment

Abstract: Research has shown a positive correlation between time spent on homework and learning. However, students often engage in off-task behaviors to escape the demands of homework. Youth with emotional or behavioral disorders (EBD) are especially likely to engage in off-task behaviors. Effective interventions to increase on-task behavior during homework are needed to increase students' academic success. Functional behavioral assessment (FBA) procedures may be helpful for intervention planning; however, there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
1
9
0
1
Order By: Relevance
“…The results showed that the application of a behavior modification principle using a shaping technique can increase on-task behavior duration in school-aged children with combined type ADHD. The results of this study support the results of several previous studies that used behavioral modification to improve on-task behavior in children with ADHD (Mathes & Bender, 1998;Hawkins & Axelrod, 2008;Athens & Vollmer, 2007;Fabiano & Pelham, 2003;Halperin & Healey, 2011). From this study's post-intervention results, we found that the participant was able to continue displaying on-task behavior for 10 minutes without any intervention.…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that the application of a behavior modification principle using a shaping technique can increase on-task behavior duration in school-aged children with combined type ADHD. The results of this study support the results of several previous studies that used behavioral modification to improve on-task behavior in children with ADHD (Mathes & Bender, 1998;Hawkins & Axelrod, 2008;Athens & Vollmer, 2007;Fabiano & Pelham, 2003;Halperin & Healey, 2011). From this study's post-intervention results, we found that the participant was able to continue displaying on-task behavior for 10 minutes without any intervention.…”
Section: Discussionsupporting
confidence: 88%
“…One large influence on academic achievement is student on-task behavior and attention (Frazier, Youngstrom, Glutting, & Watkins, 2007;Rudasill, Gallagher, & White, 2010). Thus to improve academic achievement, many teachers and interventions have aimed to increase on-task behavior or time-on-task (Amato-Zech, Hoff, & Doepke, 2006;Hawkins & Axelrod, 2008;Riley, McKevitt, Shriver, & Allen, 2011). Emerging evidence suggests that one way to increase on-task behavior is through increasing physical activity opportunities during the school day (Grieco, Jowers, & Bartholomew, 2009;Mahar, et al, 2006;Pellegrini, 1995;Pellegrini & Davis, 1993).…”
mentioning
confidence: 99%
“…Research has shown that FBA is an effective means of understanding the function of a student's problem behavior and designing behavioral interventions that address it (Ingram, Lewis‐Palmer, & Sugai, ; Kern, Delaney, Clarke, Dunlap, & Childs ; Newcomer & Lewis, ; Penno, Frank, & Wacker ). Using FBA methods, scholarly work has demonstrated that the two most common reasons why students exhibit disruptive classroom behaviors are to gain attention from others (i.e., positively reinforced attention‐maintained disruptive behavior) or escape/avoid aversive academic tasks (i.e., negatively reinforced escape‐motivated disruptive behavior) (Hawkins & Axelrod, ; McIntosh, Horner, Chard, Dickey, & Braun, ; VanDerHeyden, Witt, & Gatti, ).…”
mentioning
confidence: 99%